Uma aplicação de produto alternado em R³ usando vetores - Santos, Edson Henrique dos (2017)
In this work, we will present vectors from its relation with a oriented segment, its main operations, linear combination, linear dependence and base, up to the alternating product part. We relate the alternating product of two vectors with the area of the parallelogram formed by them, as well as the alternating product of three vectors with the volume of the parallelepiped. We also show that the vector product and the mixed product are special cases of alternating product.